2018
DOI: 10.24925/turjaf.v6i5.561-569.1768
|View full text |Cite
|
Sign up to set email alerts
|

Kiraz ve Kayısı Ağacı Reçinelerinden Elde Edilen Yenilebilir Filmlerin Çilek (Fragaria ananassa) ve Yenidünya (Eriobotrya japonica) Meyvelerinin Kaplanmasında Kullanımları

Abstract: The gum exudates leaking from cherry and apricot trees were used as edible coating material in this study. Some chemical properties of these gums were analysed whether they are proper as edible coating or not. Carbon, hydrogen, nitrogen and sulfur percentages were determined by elemental analysis. Both two gums were found rich in phenolic content and their antioxidant capacities were detected high as a result of the analysis. The behaviours against the heat and losses of weight of the films extracted from gums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Although they have a favourable chemical, nutritional and sensorial profile, strawberries can suffer interference from intrinsic and extrinsic factors that alter its characteristics. Evidence has already suggested that the concentration of nutrients and compounds in strawberries can increase and/or decrease according to the cultivation system (Abountiolas et al, 2018), stage of maturation (Boonyakiat, Chuamuangphan, Maniwara, & Seehanam, 2016), climate conditions (Akhtar& Rab, 2015), preservation methods (Ergin, Yaman, & Dilek, 2018) and storage methods (Maksimović et al, 2015). Factors characteristic of the cultivar, such as the genetic profile, may also influence strawberry composition, as already demonstrated in the literature.…”
Section: Introductionmentioning
confidence: 81%
“…Although they have a favourable chemical, nutritional and sensorial profile, strawberries can suffer interference from intrinsic and extrinsic factors that alter its characteristics. Evidence has already suggested that the concentration of nutrients and compounds in strawberries can increase and/or decrease according to the cultivation system (Abountiolas et al, 2018), stage of maturation (Boonyakiat, Chuamuangphan, Maniwara, & Seehanam, 2016), climate conditions (Akhtar& Rab, 2015), preservation methods (Ergin, Yaman, & Dilek, 2018) and storage methods (Maksimović et al, 2015). Factors characteristic of the cultivar, such as the genetic profile, may also influence strawberry composition, as already demonstrated in the literature.…”
Section: Introductionmentioning
confidence: 81%
“…Wood resin is a natural adhesive substance secreted to cover mechanical wounds that occur in tree trunks and branches (Jones & Smith, 1949;Marques & Xavier-Filho, 1991;Simas-Tosin et al, 2010). In addition, trees resins occur naturally to curing wounds caused by microbial infection, insect attacks, or water stress (Simas-Tosin et al, 2010;Liu et al, 2016;Ergin et al, 2018).…”
mentioning
confidence: 99%
“…Furthermore, the coated samples had better organoleptic properties than the controls. Overall, Ergin et al (2018) concluded that cherry gum and PAGE are suitable to coat fruits.…”
Section: Food Applicationsmentioning
confidence: 99%
“…EC 50 , the concentration required for 50% inhibition, was used to estimate the antiradical activity of PAGE by Ergin et al. (2018). A smaller value of this parameter shows a more antiradical activity.…”
Section: Functional Propertiesmentioning
confidence: 99%
See 1 more Smart Citation